PENINGKATAN HASIL BELAJAR DAN MOTIVASI BELAJAR MATA PELAJARAN IPAS EKOSISTEM MELALUI METODE PJBL SISWA KELAS 3 SD - Marniatin, Viki; Arianti, Arin; Suwarni, Suwarni (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This study aims to improve students’ learning motivation and achievement in the Natural and Social Sciences (IPAS) subject through the application of the Project-Based Learning (PjBL) method among Grade III students at SD Negeri Mranggen 02 Polokarto. The background of the study shows that IPAS learning is still predominantly teacher-centered and has not fully stimulated students’ curiosity. This research was conducted as Classroom Action Research (CAR) using the Kemmis and McTaggart spiral model over three cycles. Data were collected through observation, interviews, and tests. The findings indicate a consistent increase in students’ motivation and learning outcomes across cycles. The average learning motivation improved from 65.5 in the pre-cycle to 84.2 in cycle II, while the average learning outcomes increased from 67.7 to 87.3. The implementation of the PjBL method effectively enhanced students’ active participation, critical thinking skills, and conceptual understanding through experiential learning activities.